Pagewell 2.0 : using customer research for product development - Sawhney, Mohanbir S.; Goodman, Pallavi ([London] : SAGE, 2016)
PageWell, an e-reading platform provider, was preparing to launch PageWell 2.0 to the larger full-time MBA student market after a successful trial of PageWell 1.0 in Executive MBA (EMBA) classes at the Kellogg School of Management. Research had shown that full-time MBA students would be very interested in using products that allowed electronic access to course materials everywhere and across many platforms and that allowed electronic note-taking and storage. This case examines how PageWell addressed the challenge of delivering these new features.
Originally Published in: Sawhney, M., & Goodman, P. (2014). PageWell 2.0: Using Customer Research for Product Development. 5-213-254. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; PageWell (Firm); Marketing research -- Case studies; New products -- Case studies; Marketing -- Case studies